1995
DOI: 10.1037/0012-1649.31.2.263
|View full text |Cite
|
Sign up to set email alerts
|

Making numbers count: The early development of numerical inferences.

Abstract: Two experiments examined preschool children's ability to draw inferences about numerosity from correspondences between sets. In Experiment I, 3-and 4-year-old children made numerical inferences about a hidden set from their own counts of a corresponding visible set and also from numerical information about that set stated by the experimenter. Experiment 2 contrasted a count condition with a move condition, in which children's attention was not explicitly drawn to the numerosity of the visible set. Again, child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
2
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 20 publications
1
12
2
3
Order By: Relevance
“…The data from the two conditions were therefore pooled for subsequent analysis. This finding is in marked contrast to that obtained by Sophian et al (1995). Thus, the question remained as to why some children used counting and others did not.…”
Section: Resultscontrasting
confidence: 82%
See 3 more Smart Citations
“…The data from the two conditions were therefore pooled for subsequent analysis. This finding is in marked contrast to that obtained by Sophian et al (1995). Thus, the question remained as to why some children used counting and others did not.…”
Section: Resultscontrasting
confidence: 82%
“…Consequently our tests needed to eliminate the possibility that children would use spatial similarity as a means of establishing equivalence. We achieved this by modifying the procedure used by Sophian et al (1995) where children are shown animals that go to a party by boat (one animal per boat). In the present study the boats travelled down a narrow river (only one boat wide, thereby precluding the possibility that children would use spatial matching rather than their knowledge of cardinality to establish corresponding sets).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A large body of Author's copy of the paper as accepted for publication 3 literature has explored the development of children's oral counting skills (e.g., Bruce & Threlfall, 2004;Fuson, 1992a;Fuson, 1992b;Threlfall, 2008), the development of children's counting competencies (e.g., Bialystok & Codd, 1997;Fuson, 1992b;Gelman & Greeno, 1989;Greeno, Riley & Gelman, 1984), and the use of counting as a calculation and problem solving strategy by children of different ages and attainment in mathematics (e.g., Lefevre et al, 2002;Siegler, 2006;Siegler & Robinson, 1982;Sophian, Wood & Vong, 1995). However, there has not been much attention to children's learning of oral counting in steps bigger than 1 (e.g., counting in steps of 2, 5 or 10) and to how children develop this skill into processes that can support their calculations, despite the acknowledged significance of such counting skills (often referred to as "step" or "skip" counting) for mental calculation (Anghileri, 2008;Thompson, 2008).…”
Section: Introductionmentioning
confidence: 99%